Sosialisasi Mengenai Program Pemberdayaan Remaja Melalui Kegiatan Kepemudaan yang Positif dan Berpengaruh untuk Melawan Pergaulan Bebas Remaja - Niagara, Serena Ghean; Hidayat, Candra Nur (Jurnal Loyalitas Sosial: Journal of Community Service in Humanities and Social Sciences, 2025)
The issue of juvenile delinquency and free association among teenagers is a major concern at SMA Negeri 2 Cibinong. Based on intensive discussions with school stakeholders, the lack of youth empowerment through positive activities is identified as a core issue. This Community Service Program (PKM) aims to raise awareness and understanding about the importance of youth engagement in character-building activities to prevent risky behaviors. The method used includes mentoring through brainstorming, counseling, and education to broaden students’ perspectives on the negative impacts of free association and the benefits of active participation in positive youth programs. The result shows an increased understanding among students regarding youth empowerment and greater involvement from the school community in supporting such programs. In conclusion, participatory and educational approaches are effective in enhancing awareness and active roles of students and the school community. It is recommended that similar programs be carried out continuously with involvement from parents, teachers, and local communities to strengthen the impact.